675 Goal setting by adolescents with cerebral palsy – a qualitative service review - Krishnan, Aishwarya; Gladstone, Melissa; Mithyantha, Renuka; Sule, Reshma (Archives of disease in childhood, 2022)
AimsCerebral palsy (CP) is a disorder of movement and posture1 due to a defect or lesion of the immature brain it requires treatments and therapies from a young age which would need to be carried out throughout their lives. Around 2 per 1000 live births are diagnosed in the UK.2 Goal setting is a recommended part of therapy and is being used more commonly to help patients when planning their treatments and therapies. From previous studies,3 when patients became teenagers, their autonomy was a priority that patients with CP highlighted. However, most of these studies were focused on young children and were conducted outside of the UK.4 In order to address minimal research on goal setting in teenagers, a thematic analysis was conducted on patients with CP to ascertain whether goal setting was a beneficial addition to their therapy.MethodsA qualitative approach was used in the form of using semi-structured interviews. These interviews were conducted virtually on zoom and teams and asked questions on their experience goal setting, their expectations and changes they have experienced as patients. These teenagers were found by contacting healthcare staff and providing an information leaflet which was then distributed to teenagers with cerebral palsy (12-18 age) and their parents. Inclusion criteria set out involved the ability to communicate their views, an intellectual age of greater than 5 years old and being within Alder Hey Children’s hospital.ResultsOverall 3 interviews were conducted, recorded and analysed using thematic analysis. This helped identify multiple themes which then were grouped into 4 main themes: (1) relationship with healthcare staff, (2) Independence, (3) Motivation and (4) Participation.The first theme identified comfort that participants had with their doctors and physiotherapists and the impact it had. The second theme explored the independence felt when making decisions on their treatments and the impact of that on their confidence. The third theme recognised motivation to complete their treatment encourage them to be more motivated in daily activities as well. The final theme identified involvement when making decisions.Abstract 675 Figure 1ConclusionOverall, it was identified that goal setting had a positive impact on the quality of life-based on this short evaluation and the participants have felt like they can get involved when making decisions regarding their goals. They were also well informed about what goal setting involved and where to go if they had any questions. A larger qualitative study will need to be conducted covering a larger region and more participants in order to power the study.ReferencesCerebral palsy 2020. https://www.cerebralpalsy.org.uk/Colver et al, 2014; Sewell et al, 2014; Sellier et al, 2016; NICE, 2017a; BMJ Best Practice.Davis E, Shelly A, Waters E, Mackinnon A, Reddihough D, Boyd R, Graham HK. Quality of life of adolescents with cerebral palsy: perspectives of adolescents and parents. Dev Med Child Neurol. 2009 Mar.Schwellnus H, King G, Baldwin P, Keenan S, Hartman LR. A Solution-Focused Coaching Intervention with Children and Youth with Cerebral Palsy to Achieve Participation-Oriented Goals. Physical & Occupational Therapy In Pediatrics 2020.